Study of Serum Magnesium Levels in Type 2 Diabetics - kumar GK, Ranjith; P, Santhosh (International Journal of Medical Research and Review, 2015)
Introduction: A prospective case control study of serum magnesium levels in relations with micro & macro vascular complications of type 2 diabetes mellitus in J.L.N Hospital Ajmer. Methods: 25 patients of type 2 diabetes mellitus admitted to J.L.N Hospital were included in the study. Also 25 non diabetic patients admitted at the same time were included in the study under the control group. Results: The present study had diabetic patients ranging from 40-80 years. The mean serum magnesium levels were 1.68 mg/dl and 2.02 mg/dl in cases and controls respectively. The mean serum magnesium levels in patients on insulin, OHAs and on OHAs plus insulin were 1.43 mg/dl, 2.14 mg/dl and 1.53 mg/dl respectively. The mean serum magnesium levels in patients with controlled diabetes were 2mg/dl and 1.33 mg/dl in patients with uncontrolled diabetes. The mean serum magnesium levels in patients with and without diabetic retinopathy were 1.44 mg/dl and 2.11 mg/dl respectively. Whereas the mean serum magnesium levels in patients with diabetic nephropathy were 1.31 mg/dl and 2.08 mg/dl in those without nephropathy. Conclusion: Hypomagnesemia is a factor in type 2 diabetes and associated with various complications and duration of diabetes leading to various complications. Hence it is worth measuring serum magnesium levels in patients with type 2 DM and probably correlates their relationship with various complications.